Pengaruh Creative Marketing Campaign An Brand Experience Terhadap Purchase Intention Pada Konsumen Susu Mbok Darmi Di Kota Bogor - Amelia Junaedi Putri; Dewi Trirahayu (Universitas Pakuan, 2026)
THE EFFECT OF CREATIVE MARKETING CAMPAIGN AN BRAND EXPERIENCE ON PURCHASE INTENTION IN MBOK DARMI MILK CONSUMERS IN BOGOR CITY The local dairy beverage industry in Indonesia faces increasingly intense competition, particularly in urban areas such as Bogor City, requiring small and medium enterprises (SMEs) to optimize marketing strategies that effectively drive consumer Purchase Intention. This study aims to analyze the influence of Creative Marketing Campaign and Brand Experience on Purchase Intention among consumers of Susu Mbok Darmi in Bogor City, both partially and simultaneously. A quantitative approach with a causal research design was employed. Data were collected through questionnaires distributed to 100 respondents who met the criteria of being at least 17 years of age and having purchased or consumed Susu Mbok Darmi, selected using a purposive sampling technique. Data were analyzed using validity tests, reliability tests, classical assumption tests, multiple linear regression, t-tests, and F-tests with the assistance of SPSS version 29. Partial test results indicate that Creative Marketing Campaign has a positive and significant effect on Purchase Intention (t = 8.467; sig. < 0.001), and Brand Experience has a positive and significant effect on Purchase Intention (t = 3.214; sig. = 0.002). Simultaneous test results show that both variables jointly exert a positive and significant effect on Purchase Intention (F = 54.442; sig. < 0.001), with a coefficient of determination (R²) of 52.9%, indicating that the two variables together explain 52.9% of the variation in Purchase Intention. These findings indicate that the more creative and consistent the marketing campaign and the more positive the Brand Experience perceived by consumers, the higher their Purchase Intention toward Susu Mbok Darmi products. These results are expected to serve as an empirical basis for SMEs in developing more effective creative marketing and Brand Experience strategies to strengthen consumer Purchase Intention.